STUDI ANALISIS EFISIENSI DAN KEHILANGAN AIR PADA SALURAN IRIGASI KAMPUNG REJE GURU KECAMATAN BUKIT KABUPATEN BENER MERIAH - Fadhliani; Nanda Savira Ersa; Adhan Palaguna; Nura Usrina; Muthmainnah (Lingkar: Journal of Environmental Engineering, 2023)
D.I. Reje Guru is an open system irrigation network located in Bukit District, Bener Meriah Regency, Aceh Province. Various problems were identified such as cracked lining and wild vegetation around the network. These issues have impact on water losses along the channels’ conveyances through evaporation, seepage, operational factors and leakage. The input – output discharge measurement is used to determine the water loss and the value of the efficiency of water distribution in the Irrigation network. In addition, the evaporation and seepage loss are also calculated to find out the percentage of the loss from these two factors. The results shown that the maximum and minimum loss is from BS3RG and BS4RG which are 0,027 m3/sec and 0,004 m3/sec, respectively. The values are correlated to the efficiency values which are the highest 84,23% from BS4RG and 36,908% from BS3RG. It is confirmed that the two factors of evaporation and seepage are not the significant factor to the conveyance water loss.